Analysis of The Impact of Environmental, Social, & Governance (ESG) Disclosure and Profitability on Firm Value (Study on Banking Sector Companies Listed on The IDX From 2017-2021) - Bayuaji, Kencana; Ukhriyawati, Catur Fatchu; Putra, Rizki Eka (Green Publisher Indonesia, 2025)
The capital market is an effective means to accelerate national development through long-term fundraising that is channeled to the productive sector. Companies that go public reflect their value through the price of the shares traded, thus attracting investors to invest capital in order to achieve maximum returns. This study focuses on the influence of company performance on stock returns as measured using financial ratios such as ROA, PER, QAI, DER, NPM, EPS, and EVA on telecommunications sector companies on the Indonesia Stock Exchange during the period 2017–2021. In addition, the implementation of ESG (Environmental, Social, and Governance)-based investments is also the main highlight in increasing company value in a sustainable manner. ESG encourages transparency and corporate sustainability in line with the Sustainable Development Goals (SDGs). The results show that the company's performance measured by various financial ratios has a diverse relationship with stock returns, indicating the need for an integrated strategy between financial performance and company sustainability to attract investors while increasing the company's competitiveness in the capital market.